ETIQUETTE FORMULAE IN THE EPISTOLARY NOVEL - A. A. Resenchuk; M. Y. Ryabova (Вестник Кемеровского государственного университета, 2013)
The article deals with distinctive features of the epistolary novel genre, speech etiquette formulae are analysed and the definition of speech etiquette is provided. The basic features of address, greetings and farewell formulae in the English language are analysed, the material for analysis being novels by S. Richardson and A. Behn.